The influence of demographic factors, tax knowledge and tax ethics on tax compliance among salaried taxpayers in Seremban - Azlina, Ismail (2018)
Convincing taxpayers to comply with the tax regulations has been the main challenge of Malaysia authority. Even though tax is one of important revenue source in Malaysia, tax collection has been decreased in year 2016 compared to year 2015. Tax component from employment is the second largest contributor to Government tax revenue. The main purpose of this study is to examine the effect of demographic factors (gender, age, education background, income level and ethnicity diversity), tax knowledge and tax ethics on individual salaried taxpayer by using survey method towards tax compliance behaviour in Malaysia. A total of 500 questionnaires were distributed among Seremban taxpayers during Hasil4U programme 2016 (March – April 2016) in Inland Revenue Board of Malaysia (IRBM) Seremban Branch. Age group, tax knowledge and ethics have positive relationship with level of tax compliance behaviour among individual taxpayers in Seremban; whilst, gender, education level, income level and ethnicity affect tax compliance behaviour negatively. Overall, the findings in this paper are supported by other studies in literatures.